Design and development of synonym battlefront: a gamified approach to enhancing vocabulary diversity in academic writing - Jafri, Fakhira; Rich Joseph, Stefanie Natasha; Robert, Cindy; Amir Abdullah, Adeena Mazwa Rabytah (Universiti Teknologi MARA, 2025)
This paper presents the conceptualisation, design and development process of Synonym Battlefront, a board game aimed at addressing the challenge of insufficient vocabulary knowledge among non-native English-speaking university students, particularly in the context of academic writing. While vocabulary diversity is essential for academic success, many students face challenges related to vocabulary repetition, often stemming from restricted lexical awareness and constrained language repertoires. To tackle this, this study introduces gamified strategies to promote synonym usage through an engaging and interactive gameplay experience. Using iterative design processes and playtesting, the game was evaluated for its efficacy in enhancing vocabulary diversity and academic writing proficiency. The findings demonstrate the potential of educational game design to overcome language learning challenges, foster meaningful engagement, and support academic success. The results underscore the transformative potential of educational game design in addressing language acquisition challenges, fostering sustained learner engagement, and contributing to academic success in higher education contexts.